Interfacing porphyrins and carbon nanotubes through mechanical links - De Juan-Fernandez, Leire; Münich, Peter Wilhelm; Puthiyedath, Arjun; Nieto-Ortega, Belen; Casado, Santiago; Ruiz-Gonzalez, Luisa; Perez, Emilio M.; Guldi, Dirk Michael (Chemical Science, 2018)
We describe the synthesis of rotaxane-type species composed of macrocyclic porphyrin rings mechanically interlocked with SWCNT threads. The formation of mechanically interlocked SWCNTs (MINTs) proceeds with chiral selectivity, and was confirmed by spectroscopic and analytical techniques and adequate control experiments, and corroborated by high-resolution electron microscopy. From a thorough characterization of the MINTs through UV-vis-NIR absorption, fluorescence, Raman, and transient absorption spectroscopy we analyse in detail the electronic interactions of the porphyrins and the SWCNTs in the ground and excited states.
CRIS-Team Scopus Importer:2022-04-14